CLASSIFICATION OF PRODUCTS AND SERVICES TO SUPPORT BUSINESS PROCESS ENGINEERING AND E-COMMERCE - Reusch, Peter J. A.; Reusch, Pascal (International Journal of Computing, 2014)
Decades ago individual approaches to classify products and services had been introduced within companies to unify products and to reduce stocks and costs. Other approaches had been introduced to support international trade and tariff systems. Today new approaches are introduced to support e-commerce and improve business processes. All these approaches are different in the way how to classify, what to classify, and what results to get – and the language they use. The harmonization of all these approaches is very difficult. But especially companies that want to take part in B2B-business need bridges between the different approaches. In this paper we first present a new XML-based system to remove the language barrier within classification systems and to improve data exchange. In the second part we present an implementation of classification systems based on topic maps according to the XTM standard to implement single classification systems and establish mappings between corresponding classes of different classification systems.